Brief presentation of a mandibular overdenture over bendable abutments - A technical note - A.C. Lorenz-Vieira, DDS; R.C. Cecato, DDS, MSc; R. Michels, DDS, MSc; C.A.M. Benfatti, DDS, MSc, PhD (Elsevier, 2021)
Aim: To describe an immediate loading of a mandibular overdenture retained by a new system that allows rehabilitation using angulation up to 20°.